The exploration of local modernist furniture design and making practices with reference to Cyprus’ status as a colony, from the perspective of the maker. - Korae, Eva; Achilleos, Konstantina Niina; Venäläinen, Tuomas (My University, 2023)
The exploration of local modernist furniture design and making practices with reference to Cyprus’ status as a colony, from the perspective of the maker. While studying and restoring furniture in Cyprus, the researchers-- artisans and designers themselves-- have come across milk crates and sugar bags hidden under layers of stylized faux materials. When makers look at artefacts, they read the objects through their shapes, materials and comprehend information from unwritten nuances. They have also discovered seals, monograms as well as the inscriptions “Famagusta” and “Made in England” on the same piece of furniture. This acts as an indication of active trading between Cyprus and its then motherland. At the same time it appears that they were not trading actual furniture, but that the packaging from other goods was most probably used as raw material to make other furniture. Looking into this utilisation of materials today, we see repurposing, a sustainable practice. However, these objects enclose the context of their time along with colonial hierarchy. Regulations of the British colonial rule, prioritising, grading and taxing local timber, formed the material palette accessible to craftsmakers in Cyprus. The use of resources was dictated by the colony, underlining the maker's socio-economic status in their attempt to transform from traditional ways of life to modern. Modernist design encloses a metamorphosis from traditional lifestyle to modern along with the industrial era, the appearance of design/designer who is considered more sophisticated than the maker, an inaccuracy that still lures in the art, craft & design discourses. In a colonial context, this switch from indigenous artefacts to imperial style furniture includes a complexity of dynamics between style and social status. Nonetheless, we have to note that the British presence on the island did not only have negative influence. We study the changes in production with the launch of imported timber and the arrival of machinery in carpenter workshops.